Extensional Tectonic Investigation based on Gravity and Magnetic Data Analysis in the Gulf of Tomini, Indonesia (Rudarsko-geološko-naftni zbornik, 2023)
The enigmatic genesis of Sulawesi Island remains a debate among earth scientists up to the present day. The Northern Arm of Sulawesi is designated as a volcanic province, while the Eastern Arm is identified as an ophiolite zone along with several micro continental fragments. However, the tectonic relationship in the marine area between these two arms is not clearly defined. The existence of isolated volcanic islands, namely the Una-Una and Togian islands increases the complexity of the area. A regional study utilizing gravity and magnetic methods is needed in the Gulf of Tomini, North Sulawesi, Indonesia. Therefore, a comprehensive analysis was conducted, involving 3D inverse modelling and Moho depth estimation based on the Parker-Oldenburg algorithm using 3D Euler deconvolution to obtain the average depth of causative bodies. As a result, the presence of extensional tectonics were revealed and identified as multiple parallel dextral strike-slip faults across the study area. All of these faults show northwest-southeast lineaments consistent with the existing seismic sections. The extensional tectonic mechanism triggers crustal thinning and rifting, leading to the build-up of graben structures such as the Gorontalo, Tomini, and Poso basins. Additionally, it influences volcanic activity around the Togian and Una-Una islands. The major axes of the inferred opening area are oriented in the northeast-southwest direction, perpendicular to the lineaments of these faults. The opening area coincides with the orientation of Lalanga and Togian ridges. Finally, a regional geological structure is proposed across the Gulf of Tomini linking both the Northern and Eastern arms of Sulawesi.